Ammonia Oxidation by the Arctic Terrestrial Thaumarchaeote Candidatus Nitrosocosmicus arcticus Is Stimulated by Increasing Temperatures - Ricardo J. Eloy Alves (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Melina Kerou (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Anna Zappe (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Romana Bittner (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Sophie S. Abby (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Heiko A. Schmidt (Center for Integrative Bioinformatics Vienna, Max F. Perutz Laboratories, Medical University of Vienna); Kevin Pfeifer (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Christa Schleper (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna) (Frontiers in Microbiology, 2019)
The abstract is available here: https://uscholar.univie.ac.at/o:1079444 The abstract is available here: https://uscholar.univie.ac.at/o:1079444